2021
DOI: 10.1007/s40820-021-00629-z
|View full text |Cite
|
Sign up to set email alerts
|

A Natural Polymer Captor for Immobilizing Polysulfide/Polyselenide in Working Li–SeS2 Batteries

Abstract: SeS2 has become a promising cathode material owing to its enhanced electrical conductivity over sulfur and higher theoretical specific capacity than selenium; however, the working Li–SeS2 batteries have to face the practical challenges from the severe shuttling of soluble dual intermediates of polysulfide and polyselenide, especially in high-SeS2-loading cathodes. Herein, a natural organic polymer, Nicandra physaloides pectin (NPP), is proposed to serve as an effective polysulfide/polyselenide captor to addres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 82 publications
(82 reference statements)
0
7
0
Order By: Relevance
“…In this way, combining S and Se to rationally balance the flaw but complementary feature of these two elements has been investigated to enhance battery performance, which is represented as selenium-sulfur composite (Se x S y ) electrode. [153,154] Till now, a large quantity of work has been devoted to develop the Li-Se x S y , [155,156] Na-Se x S y , [157,158] and K-Se x S y batteries, [159,160] while the reaction mechanism and electrochemical properties of Zn-Se x S y aqueous batteries are rarely reported to our knowledge.…”
Section: Zinc Selenium-sulfur Batteriesmentioning
confidence: 99%
“…In this way, combining S and Se to rationally balance the flaw but complementary feature of these two elements has been investigated to enhance battery performance, which is represented as selenium-sulfur composite (Se x S y ) electrode. [153,154] Till now, a large quantity of work has been devoted to develop the Li-Se x S y , [155,156] Na-Se x S y , [157,158] and K-Se x S y batteries, [159,160] while the reaction mechanism and electrochemical properties of Zn-Se x S y aqueous batteries are rarely reported to our knowledge.…”
Section: Zinc Selenium-sulfur Batteriesmentioning
confidence: 99%
“…The porous nanofiber construction also improves the flexibility and ensures uninterrupted channels for fast ionic and electronic transfer (Figure a). In another study, Wu’s team developed a 3D dual-carbon framework comprising CNTs enveloped in nitrogen-rich carbon foam (CF@CNTs, Figure b) . Created to act as the host for both the SeS 2 cathode and the Li metal anode, this structure yielded reliable electrochemical behavior.…”
Section: Engineering Host Materialsmentioning
confidence: 99%
“…(b) Schematics of the fabrication of CF@CNTs-NPP. Reproduced with permission from ref . Copyright 2021 Shanghai Jiao Tong Univ Press.…”
Section: Engineering Host Materialsmentioning
confidence: 99%
“…Recently, it has been shown that doping a small amount of Se into S molecules improves the electronic conductivity of sulfur molecules, and the formation of Se−S bonds between them stabilizes the composite sulfur cathode, thus improving the electrochemical performance of Li−S batteries [36] . SeS 2 has become a new type of lithium‐ion battery cathode due to its high specific capacity of sulfur and good electrical conductivity of selenium [37–41] . In this work, we prepared SeS 2 /KB modified battery separators by compounding a small amount of SeS 2 with KB and introducing it into the positive side of lithium‐sulfur secondary battery separators.…”
Section: Introductionmentioning
confidence: 99%
“…[36] SeS 2 has become a new type of lithium-ion battery cathode due to its high specific capacity of sulfur and good electrical conductivity of selenium. [37][38][39][40][41] In this work, we prepared SeS 2 /KB modified battery separators by compounding a small amount of SeS 2 with KB and introducing it into the positive side of lithiumsulfur secondary battery separators. The physical barrier effect on polysulfide formed by the pore-like structure of KB stacking, coupled with the chemical trapping effect of SeS 2 on polysulfide, the two synergistically can effectively prevent the shuttle effect on sulfide and promote the long-term stable cycle of lithium-sulfur batteries.…”
Section: Introductionmentioning
confidence: 99%